Association between atrial fibrillation and hip fractures and the implications for hip fracture patients: a systematic review. Issue 4 (18th October 2019) - Abu‐Assi, Rabieh; Campbell, Jed; Bacchi, Stephen; Gill, Tiffany K.; George, Daniel; Chehade, Mellick
Abstract: Background: Atrial fibrillation (AF) and hip fractures are both prevalent in the elderly population. The aim of this study was to systematically review the literature regarding the association between AF and hip fractures, and the impact of AF on hip fracture prognosis. Methods: The literature search was performed using PubMed, MEDLINE, Embase and Scopus. Inclusion was based upon the application of eligibility criteria in duplicate prior to data extraction with a standardized form. Results: A total of 42 studies met the inclusion criteria. AF prevalence was found to vary between 6.5% and 35% in cohorts. Large studies with broad inclusion criteria found the prevalence of AF in hip fracture patients to be approximately 12–15%. There were conflicting results as to whether patients with AF have an increased rate of hip fractures, as compared to patients without AF. Several studies demonstrated that hip fracture patients with AF have increased rates of mortality, both as an inpatient and following discharge, and increased readmission rates. Conclusion: AF and hip fractures frequently coexist, and there is evidence to suggest AF is associated with increased readmission and mortality rates in hip fracture patients. Elements of the relationship between AF and hip fractures remain uncertain and further prospective studies on AF and hip fracture cohorts may clarify this relationship. Interventional studies targeting hip fracture patients with AF may be beneficial. Abstract : Atrial fibrillation (AF) and hip fractures frequently coexist, and there is evidence to suggest that AF predisposes to increased mortality in hip fracture patients. Some studies have also established hip fractures as a risk factor for perioperative and future AF development. Furthermore, well‐designed prospective studies on AF cohorts and hip fracture cohorts are required in order to establish the association.